Tailoring atomic diffusion for in situ fabrication of different heterostructures - Hui Zhang (Nature Portfolio, 2021)
Atomic diffusion is a powerful tool for the synthesis of heterostructures, even though controlled atomic diffusion is difficult to achieve. Here, the authors control solid-solid atomic diffusion between an Ag nanowire and a Te nanowire, producing 1D heterostructures by applying an electrical bias inside a TEM.